The Influence of Emotional Intelligence on Turnover Intention Mediated By Well-Being In Smart Gps Employees In Padang - Rahayu, Mayang Ariami Adelia; Chichi, Andriani (Universitas Negeri Padang, 2024)
This study aims to examine: (1) the effect of emotional intelligence on turnover intention (2) the effect of emotional intelligence on well-being (3) the effect of well-being on turnover intention (4) the effect of emotional intelligence on turnover intention mediated by well-being. This research is a causal research. The population of this study were all employees of Smart GPS Padang with 50 employees. The number of samples used was 50 employees who were taken using total sampling technique. Data collection using a questionnaire with a Likert scale. The analysis technique used through SmartPLS 4 software. The results of data processing in this study indicate that: (1) emotional intelligence has a negative and significant effect on turnover intention in Smart GPS Padang employees (2) emotional intelligence has a positive and significant effect on well-being in Smart GPS Padang employees (3) well-being has a negative and significant effect on turnover intention in Smart GPS Padang employees (4) emotional intelligence has a negative and significant effect on turnover intention mediated by well-being in Smart GPS Padang employees.